(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research addresses the role of party divisions in Syria’s political life, takes from the experience of the Syrian Communist Party as a primary case study, due to the party’s unique history of being subject to political divisions, that lead to the advent of new political parties, that played influential role in the political scene in Syria, and became later one of the cornerstones of Syria’s diversity both regarding its political scene and its party composition. This research examines the motivations of these defections and divisions among members of the Communist Party. It is worth noting among the leading motivations was practices, such as taking advantage of the party for personal gains by some members and groups inside its ranks, aiming to get more personal advantages and achievements. The research also tackles the ideological, intellectual and political orientation of the new parties that came into existence as a result of these defections. The research’s findings show the fundamental role of party divisions in political life in the Syrian Arab Republic, and further elaborate on the extent to which the newly founded parties were different from the parties they defected from. The research also examines the role of these divisions and defections in reinforcing party and political diversity in the country. It is worth noting that these new parties varied in their political orientation by either joining the government coalition or joining the Syrian opposition during different times. يتناول البحث دور الانقسامات الحزبية في واقع الحياة السياسية في سورية، ويتخذ من تجربة الحزب الشيوعي السوري أنموذجاً بحثياً، كون الحزب تعرض لانقسامات حزبية عدة، أسهمت في ظهور أحزاب سياسية جديدة أثرت في الواقع السياسي السوري، وشكلت دعامة من دعائم التعددية السياسية والحزبية في البلاد. رصد البحث دوافع الانقسامات الحزبية في صفوف الحزب الشيوعي، والتي تمحورت بشكل أساسي حول مسألة شخصنة الحزب، والدوافع الشخصية لبعض القوى والجماعات داخل صفوفه للحصول على المزيد من الامتيازات والمكاسب الحزبية، ورصد البحث أيضاً المسار التطويري للمنظومة الفكرية والسياسية للأحزاب الجديدة. وأظهرت نتائج البحث الدور الجوهري للانقسامات الحزبية في الحياة السياسية السورية، وبينت أيضاً مدى إسهام التغير في سياسة ومنظومة قيم ومبادئ الأحزاب الجديدة عن الحزب الأم في تعزيز التعددية السياسية في البلاد، الأمر الذي تمثل في ظهور أحزاب سياسية انضم بعضها إلى تحالف السلطة السياسية في البلاد، وأخرى انضمت إلى صفوف القوى المعارضة السورية عبر فترات زمنية مختلفة.